The Intrinsic Neuronal Activation of the CXCR4 Signaling Axis Is Associated with a Pro-Regenerative State in Cervical Primary Sensory Neurons Conditioned by a Sciatic Nerve Lesion - Dubový, Petr; Hradilová-Svíženská, Ivana; Brázda, Václav; Jambrichová, Anna; Svobodová, Viktorie; Joukal, Marek (International journal of molecular sciences, 2024)
CXCL12 and CXCR4 proteins and mRNAs were monitored in the dorsal root ganglia (DRGs) of lumbar (L4-L5) and cervical (C7-C8) spinal segments of naïve rats, rats subjected to sham operation, and those undergoing unilateral complete sciatic nerve transection (CSNT) on post-operation day 7 (POD7). Immunohistochemical, Western blot, and RT-PCR analyses revealed bilaterally increased levels of CXCR4 protein and mRNA in both lumbar and cervical DRG neurons after CSNT. Similarly, CXCL12 protein levels increased, and CXCL12 mRNA was upregulated primarily in lumbar DRGs ipsilateral to the nerve lesion. Intrathecal application of the CXCR4 inhibitor AMD3100 following CSNT reduced CXCL12 and CXCR4 protein levels in cervical DRG neurons, as well as the length of afferent axons regenerated distal to the ulnar nerve crush. Furthermore, treatment with the CXCR4 inhibitor decreased levels of activated Signal Transducer and Activator of Transcription 3 (STAT3), a critical transforming factor in the neuronal regeneration program. Administration of IL-6 increased CXCR4 levels, whereas the JAK2-dependent STAT3 phosphorylation inhibitor (AG490) conversely decreased CXCR4 levels. This indicates a link between the CXCL12/CXCR4 signaling axis and IL-6-induced activation of STAT3 in the sciatic nerve injury-induced pro-regenerative state of cervical DRG neurons. The role of CXCR4 signaling in the axon-promoting state of DRG neurons was confirmed through in vitro cultivation of primary sensory neurons in a medium supplemented with CXCL12, with or without AMD3100. The potential involvement of conditioned cervical DRG neurons in the induction of neuropathic pain is discussed.
Keywords: chemokin CXCL12; Sensory Receptor Cells; axon regeneration; benzylaminy; transection; Male; regenerace nervu; STAT3; potkani Sprague-Dawley; sciatic nerve; receptory CXCR4; Sciatic Neuropathy; spinální ganglia; signální transdukce; Interleukin-6; nervus ischiadicus; nervové receptory; mužské pohlaví; Sciatic Nerve; cyklamy; Chemokine CXCL12; Signal Transduction; nemoci sedacího nervu; Receptors, CXCR4; Benzylamines; krysa rodu Rattus; Animals; Nerve Regeneration; interleukin-6; AMD3100; zvířata; Rats; STAT3 Transcription Factor; transkripční faktor STAT3; Ganglia, Spinal; Cyclams; IL-6; Rats, Sprague-Dawley; pre-conditioning